2009
DOI: 10.1242/jeb.020404
|View full text |Cite
|
Sign up to set email alerts
|

A two-dimensional computational study on the fluid–structure interaction cause of wing pitch changes in dipteran flapping flight

Abstract: SUMMARYIn this study, the passive pitching due to wing torsional flexibility and its lift generation in dipteran flight were investigated using (a) the non-linear finite element method for the fluid-structure interaction, which analyzes the precise motions of the passive pitching of the wing interacting with the surrounding fluid flow, (b) the fluid-structure interaction similarity law, which characterizes insect flight, (c) the lumped torsional flexibility model as a simplified dipteran wing, and (d) the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 25 publications
6
111
0
Order By: Relevance
“…Conservation of additional dimensionless numbers (e.g. the density ratio between the air and the wing) (Ishihara et al, 2009) and wing inertia properties (i.e. wing deformation due to wing inertia force) are required to replicate the fluid-structure interaction, which is impossible to achieve in dynamically scaled robotic-wing experiments while also matching Reynolds number (Re).…”
Section: Dynamically Scaled Robotic Wing Experimentsmentioning
confidence: 99%
“…Conservation of additional dimensionless numbers (e.g. the density ratio between the air and the wing) (Ishihara et al, 2009) and wing inertia properties (i.e. wing deformation due to wing inertia force) are required to replicate the fluid-structure interaction, which is impossible to achieve in dynamically scaled robotic-wing experiments while also matching Reynolds number (Re).…”
Section: Dynamically Scaled Robotic Wing Experimentsmentioning
confidence: 99%
“…They found that aerodynamic performance was enhanced when the wing was flapped at a 1/3 of the natural frequency. Ishihara et al studied passive pitching by modeling a rigid wing that was free to pitch and were able to generate sinusoidal motions that produced enough lift to support some Diptera (Ishihara et al, 2009). A number of other studies have explored the role of wing flexibility in avian flight (Heathcote et al, 2008;Kim et al, 2008) and thrust generation (Alben, 2008;Lauder et al, 2006;.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the aerodynamic pressure is sufficient to produce the observed torsion using the static linear relation between the assumed aerodynamic pressure and the torsional stiffness of the wing (Ennos, 1988a). In our previous study (Ishihara et al, 2009), we used the flapping wing section model with a spring to model the wing torsional flexibility, and the finite element method to analyze the motion of the model wing interacting with the surrounding fluid. Under the dynamic similarity between the crane fly flight and our model flight, our model wing passively maintained a high angle of attack during the flapping translation and rotated quickly upon the stroke reversal without any prescribed pitching motion.…”
Section: Introductionmentioning
confidence: 99%